Formation of cortical plasticity in older adults following tDCS and motor training - Goodwill, Alicia M.; Reynolds, John; Daly, Robin M.; Kidgell, Dawson J. (Frontiers in Aging Neuroscience, 2013)
Neurodegeneration accompanies the process of natural aging, reducing the ability to perform functional daily activities. Transcranial direct current stimulation (tDCS) alters neuronal excitability and motor performance; however its beneficial effect on the induction of primary motor cortex (M1) plasticity in older adults is unclear. Moreover, little is known as to whether the tDCS electrode arrangement differentially affects M1 plasticity and motor performance in this population. In a double-blinded, cross-over trial, we compared unilateral, bilateral and sham tDCS combined with visuomotor tracking, on M1 plasticity and motor performance of the non-dominant upper limb, immediately post and 30 min following stimulation. We found (a) unilateral and bilateral tDCS decreased tracking error by 12–22% at both time points; with sham decreasing tracking error by 10% at 30 min only, (b) at both time points, motor evoked potentials (MEPs) were facilitated (38–54%) and short-interval intracortical inhibition was released (21–36%) for unilateral and bilateral conditions relative to sham, (c) there were no differences between unilateral and bilateral conditions for any measure. These findings suggest that tDCS modulated elements of M1 plasticity, which improved motor performance irrespective of the electrode arrangement. The results provide preliminary evidence indicating that tDCS is a safe non-invasive tool to preserve or improve neurological function and motor control in older adults.